Teaching methods and educability motors: Effectiveness in improving long-jump skills - Ida Zubaida; Ade Tuti Lestari; Bachtiar (Journal Sport Area, 2021)
This study investigates the differences in exercise teaching methods, commando teaching methods and motor skills on long jump skills. This research is conducted at SMP Negeri 17 Serang, Banten Province. The research design uses a 2 X 2 factorial. A random cluster technique is used in sampling. The number of samples taken is 40 students divided into four groups, each consisting of 10 students who are separated using the Verducci technique. Analysis of Variance (ANOVA) in two ways is used in analyzing the data and continued with the Tukey test with a significance level of a = 0.05, with the results: (1) overall there is a difference in the effect between the training style teaching method and the command style on long jump skills, (2) students who have high motor educability, the exercise style teaching method is better than the command style teaching method for long jump skills, (3) there is no significant difference in students who have low motor ability to the command style teaching method with the exercise style teaching method learning outcomes long jump skills, (4) there is a positive interaction between teaching methods and motor skills for long jump skills. This research needs to be followed up in the future to provide input to teachers and researchers. If you want to measure the motor ability of long jump learning, you can use the training teaching method to get maximum results.